2015
DOI: 10.1007/s11192-015-1612-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer science research: the top 100 institutions in India and in the world

Abstract: This paper aims to perform a detailed scientometric and text-based analysis of Computer Science (CS) research output of the 100 most productive institutions in India and in the world. The analytical characterization is based on research output data indexed in Scopus during the last 25 years period . Our computational analysis involves a two-dimensional approach involving the standard scientometric methodology and textbased analysis. The scientometric characterization aims to assess CS domain research output in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…When we compared the average ACPP values for few developed countries with few countries in South Asian region, we observed that ACPP for the Indian and world top institutions are 4.39 and 8.56, respectively. A similar result is shown in a recent work (Singh et al, 2015) [2] , which states that cited versus un-cited percentages for India and world top institutions in CS domain research are 44% and 59%, respectively.…”
Section: Empirical Analysissupporting
confidence: 89%
“…When we compared the average ACPP values for few developed countries with few countries in South Asian region, we observed that ACPP for the Indian and world top institutions are 4.39 and 8.56, respectively. A similar result is shown in a recent work (Singh et al, 2015) [2] , which states that cited versus un-cited percentages for India and world top institutions in CS domain research are 44% and 59%, respectively.…”
Section: Empirical Analysissupporting
confidence: 89%
“…The period of study was chosen to reflect the performance of Indian institutions in the most recent past, and a significant number of scientometric reports are available for different subject areas for other periods [9][10][11][12][13] . The output in the top 10 percentile was obtained for 15 different fields ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it focuses on the measurement of the impact of articles, journals, and institutions, along with the mapping of scientific areas (Leydesdorff, 2013). Examples include citation analysis (Koseoglu, Sehitoglu, and Craft, 2015), co-author analysis (Ioannidis, 2015), and the impact of institutions (Singh, Uddin, and Pinto, 2015). Thus, the importance of scientometrics is based on the possibility of identifying high impact articles and main researchers, and on recognizing emerging areas of knowledge (Hood and Wilson, 2001).…”
Section: Introductionmentioning
confidence: 99%